Bridging Language and Technical Learning: The Role of English Lab Courses in Agricultural Education at City University, Bangladesh - Riyad Md. Arefin, Sohan; Nilufa Akter (International Journal of Language and Literary Studies, 2025)
This study investigates the communicative and technical proficiency needs of students in the Department of Agriculture at City University, Bangladesh, emphasizing the importance of integrating English laboratory courses to enhance speaking and listening competencies. Employing a mixed-methods design, data were collected from 55 students through surveys and from 10 faculty members via semi-structured interviews. The survey findings indicate that students face significant challenges in delivering oral presentations and comprehending technical lectures, while expressing strong support for the introduction of English labs to boost their professional confidence. Thematic analysis of faculty interviews identified six key areas: the necessity for advanced communication support, assessment of lab effectiveness, recommended pedagogical activities (such as group discussions, role-plays, and technical vocabulary enhancement), improvements in learning outcomes, challenges in implementation (including time constraints, limited resources, and low student motivation), and the critical role of faculty training. Overall, the findings suggest that English lab courses can effectively bridge the gap between theoretical instruction and practical communication proficiency, thereby improving students’ academic performance and professional preparedness. The study recommends implementing context-specific lab activities, discipline-oriented content, and ongoing faculty development to ensure the sustainability and impact of English language laboratories in agricultural education.